Pengaruh Komposisi Serbuk Insektisida Nabati Terhadap Perkembangan Sitophilus zeamais dan Kualitas Benih Jagung (Zea mays L) - Sutisna, Irman; Noertjahyani, Noertjahyani; Mulya, Agus Surya (SINTA Journal (Science, Technology, and Agricultural), 2023)
Experimental research conducted at the sub-unit service unit office in Subang District, Subang Regency. The altitude of the experimental site is 76-100 meters above sea level and will be carried out from August 2022 to October 2022. This study aims to study the effect of the composition of vegetable insecticide powders (turmeric, pepper, Java chili) on the development of Sitophilus zeamais. and seed quality of corn (Zae mays L). The environmental design used a simple complete randomized design (CRD), consisting of A = no powder/control; B = Turmeric; C = Pepper, D = Javanese Chilli; E = Turmeric + Pepper; F = Turmeric + Javanese Chilli; G = Pepper + Javanese Chilli; H = Turmeric + Pepper + Javanese Chili ; I = Synthetic Insecticide. The results showed that the combination of vegetable insecticides had a significant effect on mortality at 7 HSA and the number of eggs at 7 HSA, 21 HSA, and 35 HSA, number of imago, number of larvae, number of pupae, percentage of damage. Seed quality and germination power. The use of vegetable insecticides in general provides an obstacle to the development of Sitophilus zeamais in the observation of mortality at 7 HSA and, the number of eggs at 7 HSA, 21 HSA, and 35 HSA, the number of imago, the number of larvae, the number of pupae and suppresses the level of damage to seed quality and germination.